Pengaruh Variasi Bahan Pengikat Alami dan Sintetis terhadap Kekerasan dan Kerapuhan Tablet - Muhammad Rezky Wahyudi; Yumna Zaida; Fiona Maulidia; Regina Nabila; Della Puspita; Nor Latifah (An-Najat, 2024)
Tablets are one of the most widely used pharmaceutical forms due to their practicality and cost-effectiveness. In the tablet formulation process, binders play an important role in ensuring appropriate hardness and friability, which are crucial in maintaining the physical quality of the tablet. This study aims to compare the effectiveness of natural and synthetic binders in enhancing tablet hardness and reducing friability. The method used is a literature review from various scientific sources. The results show that natural binders, such as starch and gelatin, can increase tablet hardness and reduce friability, making them an eco-friendly alternative. Synthetic binders, such as HPMC and PVP, are also effective but come with higher production costs. This study provides guidance for the pharmaceutical industry in selecting optimal binders for high-quality tablet formulations..